2021
DOI: 10.1177/1076029620978532
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the Factor V Leiden Mutation Arg534Gln in Western Region of Saudi Arabia: Functional Alteration and Association Study With Different Populations

Abstract: The rare Gln534 (Factor V Leiden; FVL) allele (1:169,519,049 T>C) is associated with an increased risk of venous thrombosis. The purpose of this study was to measure the prevalence of Factor V Leiden mutation in thrombophilia patients with deep vein thrombosis. Also, we investigated the functional and structural characteristics of this mutation p.(Arg534Gln) to be examined the cumulative impact on venous thrombosis risk as well correlated with different populations by Genome Wide Association Studies (GWAS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Factor V Leiden is an inherited condition that causes resistance to the anticoagulant effect of APC, which in turn increases the risk of venous thrombosis [35]. Previous research has demonstrated that FVL SNP variant (rs6025) is highly associated with the risk of VTE by using Genome Wide Association Studies (GWAS) [36]. Nevertheless, no FVL mutation was identified in all subjects in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Factor V Leiden is an inherited condition that causes resistance to the anticoagulant effect of APC, which in turn increases the risk of venous thrombosis [35]. Previous research has demonstrated that FVL SNP variant (rs6025) is highly associated with the risk of VTE by using Genome Wide Association Studies (GWAS) [36]. Nevertheless, no FVL mutation was identified in all subjects in this study.…”
Section: Discussionmentioning
confidence: 61%